Coseismic deformation and seismogenic structure of the 2024 Hualien Earthquake measured by InSAR and GNSS - Jiangtao Qiu; Lingyun Ji; Liangyu Zhu; Yongsheng Li; Chuanjin Liu; Qiang Zhao (Earthquake Research Advances)
On April 3, 2024, an M7.3 earthquake occurred in the offshore area of Hualien County, Taiwan, China. The seismogenic structure at the epicentral location was highly complex, and studying this earthquake is paramount for understanding regional fault activity. In this study, we employed ascending and descending orbit Sentinel-1 Synthetic Aperture Radar (SAR) data and utilized differential interferometry (InSAR) technique to obtain the co-seismic deformation field of this event. The line-of-sight deformation field revealed that the main deformation caused by this earthquake was predominantly uplift, with maximum uplift values of approximately 38.8 ​cm and 46.1 ​cm for the ascending and descending orbits, respectively. By integrating the three-dimensional GNSS co-seismic deformation field, we identified the seismogenic fault located in the offshore thrust zone east of Hualien, trending towards the northwest. The fault geometry parameters, obtained through the inversion of an elastic half-space homogeneous model, indicated an optimal fault strike of 196°, a dip angle of 30.9°, and an average strike-slip of 0.4 ​m and dip-slip of −2.6 ​m. This suggests that the predominant motion along the seismogenic fault is thrusting. The distribution of post-seismic Coulomb stress changes revealed that aftershocks mainly occurred in stress-loaded regions. However, stress loading was observed along the northern segment of the Longitudinal Valley Fault, with fewer aftershocks. This highlights the importance of closely monitoring the seismic hazard associated with this fault segment.